Profiling distributed connection chains. (19th February 2008) - Almulhem, Ahmad; Traore, Issa
A key challenge in network forensics arises because of 'attackers' ability to move around in the network, which results in creating a chain of connections; commonly known as connection chains. They are widely used by attackers to stay anonymous and/or to confuse the forensic process. Investigating connection chains can be further complicated when several IP addresses are used in the attack. In this paper, we highlight this challenging problem. We then propose a solution through hacker profiling. Our solution includes a novel hacker model that integrates information about a hacker's linguistic, operating system and time of activity. It also includes an algorithm to operate on the proposed model. We establish the effectiveness of the proposed approach through several simulations and an evaluation with a real attack data.